(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines some species of the Eribidae family (Peerless silkworms) found in the Eastern Fergana region, and the level of damage these species cause to the environment is given. The Erebidae family includes many other species that can be harmful to plants and agriculture. Controlling these pests often requires a comprehensive approach, which may include the use of chemical and biological control methods. The obtained results allow to find some practical and theoretical problems and solutions related to the field.